1956
DOI: 10.1039/jr9560001319
|View full text |Cite
|
Sign up to set email alerts
|

268. The action of acyl cyanides on 2- and 1 : 2-substituted indoles. Part II. Derivatives of 2-o-aminophenylindole

Abstract: The Action of Acyl Cyavtides 0% Indoles. Part I I . 1319 268. The Action of Acyl Cyanides on 2-and 1 : 2-Substituted Indoles. Part II.* Derivatives of 2-0-Aminophenylindole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1961
1961
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…It is well‐known that indole‐fused quinazolines, indolo[1,2‐ c ]quinazolines exhibit biological activities such as antibacterial and antifungal properties (Scheme ) . Since the synthesis of indolo[1,2‐ c ]quinazolines by thermal cyclization of 2‐(2‐aminophenyl)indoles with acyl cyanides followed by HCl treatment, many synthetic methods for such a hybrid scaffold are well documented . Several groups have shown that indolo[1,2‐ c ]quinazolines can be formed by condensation of 2‐(2‐aminophenyl)indoles with aromatic aldehydes and subsequent treatment with powdered KMnO 4 for oxidative cyclization .…”
Section: Methodsmentioning
confidence: 99%
“…It is well‐known that indole‐fused quinazolines, indolo[1,2‐ c ]quinazolines exhibit biological activities such as antibacterial and antifungal properties (Scheme ) . Since the synthesis of indolo[1,2‐ c ]quinazolines by thermal cyclization of 2‐(2‐aminophenyl)indoles with acyl cyanides followed by HCl treatment, many synthetic methods for such a hybrid scaffold are well documented . Several groups have shown that indolo[1,2‐ c ]quinazolines can be formed by condensation of 2‐(2‐aminophenyl)indoles with aromatic aldehydes and subsequent treatment with powdered KMnO 4 for oxidative cyclization .…”
Section: Methodsmentioning
confidence: 99%
“…(7). An amount of 8.2 g of this ester was dissolved in 20 ml of ethanol and a solution of 2.5 g WaCN in 8 ml of water was added.…”
Section: Methodsmentioning
confidence: 99%
“…Methanesulfonic acid (100 mL) by heating to 80 o C, then phosphorus pentoxide (13.5 g) was added to it with stirring until it dissolved completely. The phenylhydrazone of 2-aminoacetophenone (10.0 g, 44.4 mmol) (Kiang et al, 1956) was slowly added maintaining the temperature between 80 and 100 o C. The solution was then further heated at 85 o C for 30 min. The reaction mixture was cooled to room temperature and poured over crushed ice containing sodium hydroxide (65.0 g).…”
Section: General Procedures For the Preparation Of 2-(oaminophenyl)indmentioning
confidence: 99%